2011
DOI: 10.5296/jmr.v3i2.619
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Motivation, Job Autonomy and Turnover Intention in the Italian Healthcare: The mediating role of Affective Commitment

Abstract: Drawing on Self-Determination and Work Characteristics theories, we hypothesized that job \ud autonomy and intrinsic motivation were key exogenous variables positively related to \ud affective commitment, which in turn is negatively related to turnover intention, by \ud performing a mediating role. A sample of 442 nurses has been involved in this research. \ud Through the cross-validation technique, the results showed that the hypotheses of this study \ud were supported and affective commitment completely medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
113
1
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(134 citation statements)
references
References 59 publications
(68 reference statements)
12
113
1
8
Order By: Relevance
“…The best way of anticipating actual nurses' turnover or attrition is their intent to leave or stay and job satisfaction [3][4][5]21,23,25]. Results of previously mentioned studies were similar to the findings from this study which support that, nurses intend to leave when they are less satisfied, and intend to stay when they are more satisfied.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The best way of anticipating actual nurses' turnover or attrition is their intent to leave or stay and job satisfaction [3][4][5]21,23,25]. Results of previously mentioned studies were similar to the findings from this study which support that, nurses intend to leave when they are less satisfied, and intend to stay when they are more satisfied.…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, these results support the findings of the previously mentioned studies [3,5] and give a broader better explanation of how job satisfaction is one of the indicators to detect nurses' intention to leave. This result highlighted that being satisfied with different aspects of the job will encourage nurses to stay and decrease their intention to leave their current job in H/O area, the hospital or even the nursing profession entirely.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Job autonomy is capable of stimulating high levels of employee commitment to organization (Ahuja et al, 2007), specifically affective organizational commitment that is employee's willingness to maintain membership in organization and to work and help organization accomplish its goal (Meyer and Allen, 1991). This is further supported by results from the study of Galletta et al (2011) concerning the attractive working environment characteristics which showed that job autonomy perceived by workers was among the most important factors related to retention. Other studies also reported that job autonomy had a significant relationship with organizational commitment (Liu et al, 2010;Chu and Lai, 2011).…”
Section: Hypothesissupporting
confidence: 68%